Authorea
DOI: 10.22541/au.157954098.89011979
|View full text |Cite
|
Sign up to set email alerts
|

Trends in flow intermittence for European Rivers

Abstract: Intermittent rivers are prevalent in many countries across Europe and in Mediterranean countries outside Europe, but little is known about the temporal evolution of intermittency characteristics and their relationships with climate variability. In this study, a trend analysis is performed on the annual and seasonal number of zero-flow days, the maximum duration of dry 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Metacommunity approaches have seen particularly widespread, recent application in running water ecology, with the acknowledgment that in dynamic, dendritic systems reliable biomonitoring and conservation decision‐making depend on a consideration of both niche‐based and dispersal processes (Cid et al., 2020; Heino, 2013; Ruhi et al., 2017; Tonkin et al., 2018). These processes dictate community resistance and resilience to drying, the most fundamental form of ecological disturbance in rivers and streams (Leigh & Datry, 2017) and a prominent climate‐related driver of the freshwater biodiversity crisis (Piano et al., 2019; Reid et al., 2019; Tramblay et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Metacommunity approaches have seen particularly widespread, recent application in running water ecology, with the acknowledgment that in dynamic, dendritic systems reliable biomonitoring and conservation decision‐making depend on a consideration of both niche‐based and dispersal processes (Cid et al., 2020; Heino, 2013; Ruhi et al., 2017; Tonkin et al., 2018). These processes dictate community resistance and resilience to drying, the most fundamental form of ecological disturbance in rivers and streams (Leigh & Datry, 2017) and a prominent climate‐related driver of the freshwater biodiversity crisis (Piano et al., 2019; Reid et al., 2019; Tramblay et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the taxonomic richness of families with traits promoting resistance and/or resilience to drying (our ‘high RR’ group) responded only to impacts—not drying—but this response was weak, due to low taxonomic richness. As rivers experience increasing climate‐driven drying (Tramblay et al., 2021), our results highlight the need to develop region‐specific indices for use in ecological status assessments. By identifying priority sites for further investigation, such assessments can inform management actions that support biodiversity within dynamic river ecosystems.…”
Section: Discussionmentioning
confidence: 76%
“…By extending the widely applied flow regime concept (Poff et al., 1997) to non‐perennial streams, the conceptual drying regime framework presented here could be used to develop holistic management strategies for the >50% of global river length that dries. While recent work has found that mean annual hydrologic characteristics of non‐perennial streams have spatial coherence (Hammond et al., 2021) and are undergoing widespread change (Tramblay et al., 2021), limited focus has been on characterizing event‐scale stream drying behavior. As a result, it is unclear both how components of stream drying (duration, rate, frequency, and magnitude; Table ) vary through space and time, and how different aspects of stream drying may cascade to impact ecological and biogeochemical processes both locally and in downstream waters.…”
Section: Resultsmentioning
confidence: 99%